Scrutinizing The Method Of Contribution For Islamic Waqf Bank Fund - Muhammad Ridhwan Ab. Aziz; Mohd Asyraf Yusof (Islamic Bank Training And Research Academy (IBTRA), 2024)
Cash waqf means the dedication of some money from one's possessions and establishing an asset based on that amount and offering it to the benefit of people. It is also defined as the devotion of an amount of money by a founder and the dedication of its usufruct in perpetuity to the prescript purposes. Therefore, the study for the management of cash waqf fund is essential in order for the fund to be use efficiently. The objective of this article is to scrutinize relationship between level of income and contribution method of cash waqf fund in Islamic Waqf Bank as well as the appointment of Islamic Waqf Bank as an agent in collecting the fund. The methodology of research in this article is through a quantitative research towards 231 Muslim respondents. The general finding of this article shows that, the strong willingness among the respondents to use electronic method in contributing for Islamic Waqf Bank. It is proposed a proper channeled in contributing for waqf fund and the appointment of Islamic Waqf Bank as an agent in collecting the cash waqf fund, will be a strong tendency that the Islamic Waqf Bank’s operation will be run efficiently.